COMPARISON OF MORPHOLOGICAL AND CHEMICAL CHARACTERISTICS OF TWO SELECTED ACCESSIONS AND SIX WILD SPECIES OF GENUS Cinnamomum SCHAEFF - Ariyarathne, H.B.M.A; Weerasooriya, S.N; Senarath, W.T.P.S.K (My University, 2018)
Cinnamon is increasingly becoming an important and potential foreign exchange earner and it is the most important spice in Sri Lanka. However, currently only two selected cinnamon accessions are available in Sri Lanka. Therefore, establishment of more commercial cinnamon varieties/ cultivars with high quality and yield are required. Experiments were carried out to investigate and compare of morphological and chemical characteristics of two selected cinnamon accessions (Sri Wijaya and Sri Gemunu) and six wild cinnamon species (Cinnamomum citriodorum, Cinnamomum capparu coronde, Cinnamomum litseaefolium, Cinnamomum revulorum, Cinnamomum dubium and Cinnamomum sinharajanse). Morphological characters of flower, leaf, seed and bark, yield of bark and leaf oil, and chemical characters of leaf and bark oil were examined. Leaf morphological characters; leaf shape, type of venation, leaf apex shape, leaf length and width, petiole length and leaf area were varied among species studied. Bark color, surface texture of bark, bark odor and seed color also helped to differentiate studied species. Highest mean leaf oil percentage and bark oil percentage was obtained from C. zeylanicum (Sri Gemunu) and C. zeylanicum (Sri Wijaya) respectively. The lowest mean leaf oil percentage was obtained from C. citriodorum and the lowest mean bark oil percentage was obtained from C. dubium. GC-MS analysis indicated presence of many economically important compounds such as eugenol, cinnamaldehyde, benzyl benzoate etc., in leaf and bark oil of all studied species. Abundance of considered favorable characters which are already consisted with cultivated accessions Sri Gemunu and Sri Wijaya bark and leaf oil with important characters and easy peeling ability has been observed in tested wild types, indicating the possibilities of improvement of Ceylon cinnamon for these characters through hybridization programme using wild relatives.
Keywords: cinnamon, wild species, cultivated accessions, GC-MS analysis, bark oil, leaf oil